PEMBERATAN SANKSI PIDANA RESTITUSI BAGI GURU SEBAGAI PELAKU TINDAK PIDANA KEKERASAN SEKSUAL - Ardy Ambarkasih; Ida Budhiati; Rachmat Kurniawan Siregar (JOURNAL OF LAW AND NATION, 2023)
The imposition of a criminal sanction of restitution for a teacher who commits a crime of sexual violence, as in the case of Herry Wirawan, is a serious and important matter to be considered by the court. Sexual violence, especially when committed by a teacher who is supposed to be an authoritative and safe figure for his pupils, is a serious violation of trust and security. Strengthening criminal sanctions with restitution could be an appropriate step to have a significant impact on the perpetrators of sexual violence. Restitution in this context could mean giving compensation to the victim as a form of acknowledgement of the impact caused by the perpetrator's actions. These sanctions could be a form of justice for the victims and affirm that such acts are intolerable in society. However, it should also be considered that the lifting of criminal sanctions is not the only thing to be considered in dealing with such cases. The legal process must consider justice, rehabilitation, as well as preventive efforts to prevent such acts of violence from happening again in the future. In addition, the education system also needs to take measures to ensure the safety and protection of the students so that similar cases do not happen again. Any criminal act must be treated seriously and proportionately in accordance with applicable law, taking into account justice for victims, rehabilitation for perpetrators, and preventive efforts for a safer future for all parties involved.